Sosialisasi Pentingnya Pendidikan Tinggi dalam Rangka Memperbaiki Kualitas Hidup di Ma Ma’arif Ponggok Kabupaten Blitar - Tutut Noviana (Universitas Madani Indonesia, 2025)
Studying at a university will make students have broad insight, think forward, be critical and provide solutions so that they will produce superior human resources. However, in the East Java province, especially the Kediri Residency, the population pays little attention to the importance of higher education. Based on observations, it was found that MA Ma'arif Ponggok class XII still had many students who were less interested in continuing to college. Therefore, there is a need for socialization and motivation aimed at increasing students' interest in continuing to college. The method for community service activities uses the Service Learning (S-L) method, a learning approach that integrates learning activities and community social services. The material discussed is material related to the courses to be studied, various kinds of work that can be pursued, motivation, as well as information about Madani University of Indonesia. These outreach activities have gone well and succeeded in motivating students to continue to higher education. The survey results before the socialization were 27.6% of students' interest in entering higher education and increased to 72.4% after the socialization. The use of social media and Microsoft Office Power Point, which have become popular social media for the current generation of students, is a good support for participating in socialization. There needs to be outreach to students' parents so they can provide support. There is a need for questionnaires and in-depth interviews with students to find out more about the reasons why students are interested in entering higher education.